The Influence of Market Timing Ability, Stock Selection Skill, Fund Age, and Fund Size on The Performance of Sharia Mutual Funds - Sukarno, Agus; Oetomo, Hadi; Sutanto, Hery; Liestyana, Yuli; Herlianto, Didit (Universitas Tanjungpura, 2025)
This study aims to analyze the effect of Market Timing Ability, Stock Selection Skill, Fund Age, and Fund Size on the Performance of Sharia Equity Mutual Funds for the period January 2021 to December 2024. This type of research uses a quantitative approach. The research sample used was Islamic stock mutual funds that were active from January 2021 to December 2024 totaling 22 stock Islamic mutual funds. Samples were taken using purposive sampling method with various sampling criteria. The research data were analyzed using multiple linear regression analysis, as well as the research method using the classical assumption test, and hypothesis testing t and F. The results of hypothesis testing show that Market Timing Ability, Stock Selection Skill, Fund Age, and Fund Size have a joint effect on performance. Sharia Equity Mutual Funds for the 20121-2024 period, Market Timing Ability has no effect on the Performance of Sharia Equity Mutual Funds for the 2021-2024 period, Stock Selection Skill has no effect on the Performance of Sharia Equity Mutual Funds for the 2021-20224 period, Fund Age has no effect on the Performance of Sharia Equity Mutual Funds for the 2021-2024 period, Fund Size has no effect on the Performance of Sharia Equity Mutual Funds for the 2021-2024 period.